The extension of some Orlicz space results to the theory of optimal measure. Issue 8 (2nd January 2013) - Agbeko, Nutefe Kwami; Dragomir, Sever Silvestru
Abstract We extend some fundamental results about the Orlicz space LΦ (such as the Jensen and Hölder inequalities, the LΦ Banach spaces and their duals) to Optimal Measure Theory.